New alliances for research and teaching support: establishing the Göttingen eResearch Alliance. Issue 4 (1st September 2015) - Andrew Cox, Dr; Schmidt, Birgit; Dierkes, Jens
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe the design and implementation of policies, digital infrastructures and hands-on support for eResearch at the University of Göttingen. Core elements of this activity are to provide support for research data management to researchers of all disciplines and to coordinate on-campus activities. These activities are actively aligned with disciplinary, national and international policies and e-infrastructures. Design/methodology/approach – The process of setting up and implementing an institutional data policy and its necessary communications and workflows are described and analysed. A first assessment of service development and uptake is provided in the area of embedded research data support. Findings – A coordination unit for eResearch brings together knowledge about methods and tools that are otherwise scattered across disciplinary units. This provides a framework for policy implementation and improves the quality of institutional research environments. Practical implications – The study provides information about an institutional implementation strategy for infrastructure and services related to research data. The lessons learned allow insights into current challenges and work ahead. Originality/value – With a cross-cutting, "horizontal" approach, in the Göttingen eResearch Alliance, two research-orientated infrastructure providers, a library and an IT service, combine their services and expertise to develop an eResearch service and support portfolio for the Göttingen Campus.